Non-matrigel scaffolds for organoid cultures. (28th April 2021) - Kaur, Savneet; Kaur, Impreet; Rawal, Preety; Tripathi, Dinesh M.; Vasudevan, Ashwini
Abstract: Organoids are three-dimensional cell cultures mostly from tissue-resident or embryonic stem cells (one or multiple) on hydrogels along with defined growth factors. Currently, matrigel is the most commonly employed matrix for 3D organoid cultures. However, certain undesirable attributes of matrigel have paved the way for several other natural and synthetic hydrogel scaffolds for organoid cultures. In this review, we discuss the constraints of matrigel and describe other alternative scaffolds that have been used for organoid cultures. Given the potential of organoids in a plethora of therapeutic and pharmaceutical applications, it is indeed imperative to develop defined and customized hydrogels other than the matrigel. Highlights: BMatrigel is the most preferred hydrogel for three-dimensional organoid cultures from stem cells or tumor cells. Chemically-ill defined composition of matrigel leads to lack of reproducibility and inconsistencies in organoid growth. Natural hydrogels, like gelatin, fibrin, collagen, silk, and tissue ECM are being explored as organoid scaffolds. Stiffness, mechanical integrity, chemistry and topography of hydrogels need to be optimized for organoid cultures. Synthetic hydrogels functionalized with bioactive peptides have facilitated organoid cultures.